Vitamin D supplementation of initially vitamin D-deficient mice diminishes lung inflammation with limited effects on pulmonary epithelial integrity - Gorman, S.; Buckley, A.; Ling, K.; Berry, L.; Fear, V.; Stick, S.; Larcombe, A.; Kicic, Anthony; Hart, P. (2017)
© 2017 The Authors. Physiological Reports published by Wiley Periodicals, Inc. on behalf of The Physiological Society and the American Physiological Society In disease settings, vitamin D may be important for maintaining optimal lung epithelial integrity and suppressing inflammation, but less is known of its effects prior to disease onset. Female BALB/c dams were fed a vitamin D 3 -supplemented (2280 IU/kg, VitD + ) or nonsupplemented (0 IU/kg, VitD - ) diet from 3 weeks of age, and mated at 8 weeks of age. Male offspring were fed the same diet as their mother. Some offspring initially fed the VitD - diet were switched to a VitD + diet from 8 weeks of age (VitD -/+ ). At 12 weeks of age, signs of low-level inflammation were observed in the bronchoalveolar lavage fluid (BALF) of VitD - mice (more macrophages and neutrophils), which were suppressed by subsequent supplementation with vitamin D 3 . There was no difference in the level of expression of the tight junction proteins occludin or claudin-1 in lung epithelial cells of VitD + mice compared to VitD - mice; however, claudin-1 levels were reduced when initially vitamin D-deficient mice were fed the vitamin D 3 -containing diet (VitD -/+ ). Reduced total IgM levels were detected in BALF and serum of VitD -/+ mice compared to VitD + mice. Lung mRNA levels of the vitamin D receptor (VDR) were greatest in VitD -/+ mice. Total IgG levels in BALF were greater in mice fed the vitamin D 3 -containing diet, which may be explained by increased activation of B cells in airway-draining lymph nodes. These findings suggest that supplementation of initially vitamin D-deficient mice with vitamin D 3 suppresses signs of lung inflammation but has limited effects on the epithelial integrity of the lungs.